The Urgency of Establishing Funding Regulations for Refugees by Faith-Based Organizations in Indonesia - Fitria; Susetyo, Heru; Rahmawati, Nurlaili; Hanah, Ummu (Faculty of Law, Universitas Brawijaya, 2025)
More than 12,000 refugees in Indonesia face a life of uncertainty, as the country is not considered a destination for them. Moreover, Indonesia needs more adequate regulations regarding refugees. In practice, handling refugee issues in Indonesia relies on the United Nations High Commissioner for Refugees (UNHCR) and the International Organization for Migration (IOM). Unfortunately, most refugees cannot return to their home countries, primarily due to ongoing conflicts, with only about 1–1.5% being resettled in third countries. Consequently, they remain in Indonesia for years, even decades, without clear prospects for their future. This paper analyzes the urgency of establishing funding for refugees by civil society, mainly through faith-based organizations (FBOs), viewed through Jacques Derrida's theory. In this research, a socio-legal method was employed, which examines law through the lens of social phenomena. The research team's key findings are as follows: first, the interviewed refugees, having undergone several migrations, find themselves